Analysis of torsional vibration characteristics and time delay feedback control of semi-direct drive cutting transmission system in shearer. (March 2020) - Jiang, Song; Li, Wei; Xin, Gaifang; Sheng, Lianchao; Fan, Mengbao; Yang, Xuefeng
Abstract: The semi-direct drive cutting transmission system driven by low speed and high torque permanent magnet synchronous motor (PMSM) in shearer is a typical electromechanical coupling system. In this paper, the torsional vibration characteristics of the transmission system with internal parameter and external cutting load excitation changes are studied. Considering the torsional vibration angle and the air gap magnetic field energy of the PMSM, the torsional vibration model of the electromechanical coupling transmission system is derived by the Lagrange-Maxwell equation. Then, in the case of 1:1 internal resonance and external resonance, the first-order approximate solution is obtained by multiple scale method, and the influence of cutting load excitation and current on the torsional vibration characteristics of the rotor system is analyzed. In addition, the numerical simulation is used to study the vibration jump phenomenon of the nonlinear electromechanical coupling system. The influence of the cutting load excitation on the chaos motion is obtained by the bifurcation diagram and maximum Lyapunov index map. Finally, the vibration amplitude and chaos motion of the rotor system are suppressed by the time delay feedback controller. The research results can provide a theoretical basis for the design and manufacture of the shearer semi-direct drive cutting transmission system.